Rule based model for pneumonia (COVID-19) nursing care - S Hendra; H R Ngemba; N W Sridani; G B R Lintin; K Tantakarnapa; R Nur; M A Indrajaya (Jurnal Informatika, 2021)
Abstract. This research was conducted during the COVID-19 pandemic, when during the pandemic, many patients died. The mortality rate was caused by complications in the form of pneumonia in patients with deteriorating health conditions. This study aims to develop an inference model to become a decision support system in the enforcement of the clinical pathway of pneumonia COVID-19 nursing care. This research model is based on the application of NANDA International nursing diagnoses to determine the objectives of the Nursing Outcome Classification (NOC) and the interventions that must be carried out by the Nursing Intervention Classification (NIC). The data in this study were obtained from the results of expert interviews regarding the handling of pneumonia and medical literature on handling COVID-19 cases. The results of this study can guide the diagnosis and treatment of pneumonia caused by the COVID-19 virus, as well as a similar process that occurs with acute respiratory distress syndrome.